Práticas de enfermagem na inserção, manutenção e remoção do cateter central de inserção periférica em neonatos - Rangel, Regiane Josy Mediote (2013)
A stable and efficient venous access alternative for clinically ill newborns at the Neonatal Intensive Care Unit (NICU) that is frequently used it the Peripherally Inserted Central Catheter (PICC). This is a long and flexible catheter, which is inserted through a peripheral vein progressing to the distal third of the superior cava vein, or the inferior cava vein, acquiring central venous access propertie. Objective: To evaluate the Nursing practices at the insertion, maintenance and removal of the PICC in NBs. Methodology: This is a retrospective transversal descriptive correlational study. Data was collected from the charts and follow-up cards for the PICC in NBs, at the NICU of a University Hospital in the years of 2009, 2011, and 2012. The exclusion criteria were: NBs admited after referral from another institution, with the catheter already inserted; NBs transferred to another institution with catheter already inserted; NBs who have died while using the catheter; NBs who have had the insertion of the PICC done by another professional, and not the Nurse. Descriptive analyses were done, using t Student test, Qui-square test and ANOVA. The significance level adopted was that of 5%. Results: The population of the study was constituted by 137 NB, mainly premature (67.9%), with very low weight (35%), and extreme low weight (32.1%). For the insertion of the PICC, 1.9 Fr silicon monolumen catheters (88.3%) were used, in the cephalic (41.6%) and the basilic (32.1%) veins. The initial positioning of the catheter's tip was central in 60.6% of the cases, most frequently in the superior cava vein (34.3%). There were complications in 53.3% of the PICCs, and the most common of those were; obstruction (13.1%), infiltration and/or overflow (12.4%), and the accidental exteriorization (8.8%). The average permanence of the PICC was of 10.5 days, most commonly removed because of the end of therapy (60.3%), and infiltration or overflow (12.5%). The catheter's permanece time was influenced by the non-central positioning of the tip (p=0.001), complications (p=0.014), and the non-elective removal (p=0.005). Conclusion: This study offered knowledge about the state of the use of the PICC and the population that has received it in the healthcare unit studied. The characteristics found are similar to the ones described in the literature, although the initial malpositioning of the tip of the catheter, as well as the number of complications that determined the non-elective removal of the PICC, were highlighted, showing the need for the creation of protocols and routines, as well as educative intervention programs, in order to guarantee the patient's safety, and the quality of the assistance in NB Nursing care.